EPIDEMIOLOGY STUDY OF NPC PATIENTS IN BANGLI HOSPITAL AT 2015-2017 - Yully Prapyatiningsih (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is a malignancy of the nasopharyngeal epithelium. Nasopharyngeal carcinoma is the five positions among other malignancies. Objective: To determine the distribution of patients with nasopharyngeal cancer (NPC) in department of ENT Bangli hospital, the period during January 2015-December 2017. Material and methods: This descriptive study by collecting data from the medical record of NPC patients who come to the outpatient's clinic ENT Bangli hospital and data from the Department of Pathologic Anatomy at Bangli hospital. Results: The distribution patients with NPC was conducted from January 2015 until December 2017 there were 169 people. This research obtained the highest patients with NPC in 2016 as 67 cases. NPC based on sex in 2015 is males as 27 cases (58.70%), in 2016 is males as 43 cases (64.18%) and 2017 is males as 36 cases (64.29%). NPC based on age group is 41-50 years that in 2015 as 16 cases (34.70%), in 2016 as 27 cases (40.30%) and by age group 51-60 years in 2017 as 23 cases (41.07%). NPC patients based on stage most in stage III in 2015 as 18 cases (39.13%), in 2016 as 24 cases (35.82%) and in 2017 as 16 cases (28.57 %). NPC patients based on sex was found in stage III were males in 2015 as 14 cases, in 2016 as 16 cases and 2017 as 12 cases. NPC patients based on histopathology result at most on the WHO-3 classification, in 2015 as 44 (95.65%), in 2016 as 62 cases (92.54%) and in 2017 as 53 cases (94.64%). Conclusion: Distribution of patients with NPC in Bangli hospital from January 2015 until the highest December 2017 were 169 people. This research obtained the highest population of NPC in 2016 as 67 cases. NPC based on sex in 2016 is male as 64.18%. NPC most found by age group in 41-50 years in 2016 as 40.30%. NPC based on stage most found in stage III, in 2016 as 35.82%. NPC based on sex most found in stage III in 2016 as 16 cases. NPC based on histopathology result is WHO-3 in 2016 as 92.54%.